Statistical Study of Small-Scale Interplanetary Magnetic Flux Ropes in the Vicinity of the Heliospheric Current Sheet - Liu, Qiang; Zhao, Yan; Zhao, Guoqing (Frontiers in Physics, 2021)
The small-scale interplanetary magnetic flux ropes (SIMFRs) are common magnetic structures in the interplanetary space, yet their origination is still an open question. In this article, we surveyed 63 SIMFRs found within 6-day window around the heliospheric current sheet (HCS) and investigated their axial direction, as well as the local normal direction of the HCS. Results showed that the majority (48/63) of the SIMFRs were quasi-parallel to the associated HCS (i.e., the axial direction of SIMFRs was quasi-perpendicular to the normal direction of the associated HCS). They also showed that the SIMFRs quasi-parallel to the associated HCS statistically had shorter duration than the cases quasi-perpendicular. The results indicate that most of these SIMFRs may be generated in the nearby HCSs.